2020
DOI: 10.1186/s12885-020-06750-3
|View full text |Cite
|
Sign up to set email alerts
|

Roles of neutrophil/lymphocyte ratio in prognosis and in differentiation of potential beneficiaries in HER2-positive breast cancer with trastuzumab therapy

Abstract: Background: The relationship of neutrophil/lymphocyte ratio (NLR) to prognosis of HER2-positive breast cancer (BC) is not well studied. We aimed to assess the prognostic role of NLR in HER2-positive BC patients treated with or without trastuzumab. Methods: The clinical data of 843 HER2-positive BC patients from July 2013 to July 2018 were collected. The difference among variables was calculated by chi-square test. The associations between clinicopathological factors, NLR and disease-free survival (DFS) were an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…One recent retrospective study has compared the prognostic value of the NLR among HER2+ patients treated with or without adjuvant trastuzumab [16]. In contrast to our results, NLR was not prognostic among HER2+ patients treated without trastuzumab but showed prognostic value among the patients with 1-year adjuvant trastuzumab.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…One recent retrospective study has compared the prognostic value of the NLR among HER2+ patients treated with or without adjuvant trastuzumab [16]. In contrast to our results, NLR was not prognostic among HER2+ patients treated without trastuzumab but showed prognostic value among the patients with 1-year adjuvant trastuzumab.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, NLR was not prognostic among HER2+ patients treated without trastuzumab but showed prognostic value among the patients with 1-year adjuvant trastuzumab. The difference in the 3-year DFS rate was rather small, 95.3% vs. 90.5% for low and high NLR groups, respectively, with a rather short median follow-up time of 20 months [16]. In our study, with a long follow-up time (median 10.4 years), the prognostic impact of both NLR and MLR according to OS, BCSS and distant relapse rate was found among the HER2+ patients treated without adjuvant trastuzumab but not among those who did receive trastuzumab.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Tiainen et al (13) found that among the HER-2+ patients without trastuzumab therapy as adjuvant treatment, the survival rates of patients with high NLR were significantly lower compared with those with low NLR. On the contrary, Ding et al (14) found that NLR did not have prognostic value among HER-2+ patients without trastuzumab treatment, yet could predict the prognosis of those who received trastuzumab treatment for 1 year. Additionally, the 3-year DFS of the low NLR group was also found to be significantly higher than that of the high NLR group (95.3% vs 90.5%, P=0.011).…”
Section: Introductionmentioning
confidence: 92%
“…The inclusion criteria were as follows: (a) patients with histologically confirmed CRC; (b) patients who underwent primary tumor resection; and (c) patients who had no treatment prior to the blood test. The exclusion criteria were as follows: (a) familial adenomatous polyposis or hereditary colon cancer; (b) there were no signs of clinical infection such as fever on the day of blood collection (28), and (c) patients with other neoplastic diseases during the same period. Baseline clinicopathologic parameters, including general basic information; past, personal, and family history; preoperative and postoperative blood routine examination; serological markers and inflammation-related indicators; enhanced computed tomography (CT) and MRI; degree of histological differentiation and pathological TNM staging; KRAS and BRAF V600E mutation status and microsatellite instability (MSI) testing; and preoperative and postoperative adjuvant chemoradiotherapy, were derived from the medical records.…”
Section: Patients and Study Designmentioning
confidence: 99%